Effects of Shape Memory Alloys on Response of Steel Structural Buildings within Near Field Earthquakes Zone - Mahmoud Ahmadinejad; Alireza Jafarisirizi; Reza Rahgozar (Salehan Institute of Higher Education, 2020)
Base isolation is one of the effective ways for controlling civil engineering structures in seismic zone which can reduce seismic demand. Also is an efficient passive control mechanism that protects its superstructure during an earthquake. However, residual displacement of base-isolation systems, resulting from strong ground motions, remain as the main obstacle in such system’s serviceability after the earthquake. Shape Memory Alloys (SMA) is amongst the newly introduced smart materials that can undergo large nonlinear deformations with considerable dissipation of energy without having any permanent displacement afterward. This property of SMA may be utilized for designing of base isolation system to increase the structure’s serviceability. Here, a proposed semi-active isolation system combines laminated rubber bearing system with shape memory alloy, to take advantage of SMAs high elastic strain range, in order to reduce residual displacements of the laminated rubber bearing. Merits of the system are demonstrated by comparing it to common laminated rubber bearing isolation systems. It is found that the optimal application of SMAs in base-isolation systems can significantly reduce bearings’ residual displacements. In this study, OpenSees program for a three dimensional six-storey steel frame building has been used by locating the isolators under the columns for investigating the feasibility of smart base isolation systems, i.e., the combination of traditional Laminated Rubber Bearing (LRB) with the SMA, in reducing the structure’s isolated-base response to near field earthquake records are examined. Also, a new configuration of SMAs in conjunction with LRB is considered which make the system easier to operate and maintain.